Implicações socioambientais e jurídicas do uso da terra na planície de inundação do Arroio Cadena, Santa Maria, RS - Garcia, Medianeira dos Santos (2019)
Analyzing the socio-environmental and legal implications of land use in a flood plain area of the Cadena stream, in Santa Maria, RS, more specifically on an artificially generated river island located on its left bank, was the main objective of this thesis work. The specific objectives sought to: (1) verify the socio-environmental conditions of the area under study; (2) to identify, in the current legislation, norms that help the population that inhabits the area, with regard to improvements in living conditions; and (3) verify the population's perception of their rights and their subsidiary responsibility in relation to environmental problems and relate the population's perception to socioenvironmental and legal conditions. As a methodological basis, the proposal of the four levels of geographic research (compilatory, correlative, semantic and semantic), recommended by André Libault (1971), was used. The operational procedures for obtaining data and information consisted of bibliographic research regarding aspects related to the areas of Geography and Environmental Law; application of questionnaires, aiming to apprehend the residents' perception; interpretation of cartographic and Remote Sensing documents; and also fieldwork to identify land use and physical landscape changes. From the study of the various geographical aspects, it was concluded that, in order to improve environmental conditions, collective work between different sectors of society is necessary. The importance of the population doing its part is emphasized, aiming at an urgent change of attitudes, such as: carry out selective waste collection, help inspect and organize community associations, since these associations are direct links with the public authorities in search of the common good. Regarding the perception on the part of the residents, it is concluded that the population demonstrated to know, even if empirically, the correlations of the geomorphological transformations of the areas with the environmental quality. It became evident, after this study, the need to implement municipal public policies to implement the standards that already exist. In this context, there is a need for oversight to achieve effectiveness, enabling the individual to achieve a sustainable and dignified human development. This, according to the population, is also related to the quality of health of the population living there, since Geography seeks to understand the multiple connections within society, seeking, in accordance with the Federal Constitution, the well-being of this population, and environmental law needs to understand society and socio-environmental issues and, to that end, standardize access to goods. . Thus, the law aims to protect life, since Geography seeks mechanisms to improve the quality of life of the population in general, it was also concluded that public policies are necessary in order that the population can enjoy a environment with quality consistent with the Federal Constitution, which provides for the principle of human dignity, and it is this same law that has the premise of protecting and assisting the well-being of the population.